1993
DOI: 10.1063/1.858700
|View full text |Cite
|
Sign up to set email alerts
|

Toward a hydrodynamic theory of sonoluminescence

Abstract: For small Mach numbers the Rayleigh–Plesset equations (modified to include acoustic radiation damping) provide the hydrodynamic description of a bubble’s breathing motion. Measurements are presented for the bubble radius as a function of time. They indicate that in the presence of sonoluminescence the ratio of maximum to minimum bubble radius is about 100. Scaling laws for the maximum bubble radius and the temperature and duration of the collapse are derived in this limit. Inclusion of mass diffusion enables o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
178
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(188 citation statements)
references
References 28 publications
9
178
0
1
Order By: Relevance
“…The first contribution in this regard was made in the original paper of Gaitan et al (1992), which demonstrated that the radius of the bubble as a function of time observed experimentally exhibits the same behavior as solutions to the Rayleigh-Plesset equation (to be derived in Sec. II); subsequently, studies by Lö fstedt et al (1993Lö fstedt et al ( , 1995 confirmed and elaborated on this conclusion. The Rayleigh-Plesset theory is remarkably simple, and it captures many important features of single-bubble sonoluminescence.…”
Section: Historical Overviewsupporting
confidence: 53%
“…The first contribution in this regard was made in the original paper of Gaitan et al (1992), which demonstrated that the radius of the bubble as a function of time observed experimentally exhibits the same behavior as solutions to the Rayleigh-Plesset equation (to be derived in Sec. II); subsequently, studies by Lö fstedt et al (1993Lö fstedt et al ( , 1995 confirmed and elaborated on this conclusion. The Rayleigh-Plesset theory is remarkably simple, and it captures many important features of single-bubble sonoluminescence.…”
Section: Historical Overviewsupporting
confidence: 53%
“…As shown in Table 1, the calculated values of the maximum radius and the period for each bouncing motion are in good agreement with the observed one (Loefstedt et al, 1993) can be seen. However, the bubble radius-time curve obtained by the Rayleigh equation with a polytropic relation of P b V b 1.4 =const.…”
Section: Thermal Boundary Layer Thicknesssupporting
confidence: 75%
“…However, the polytropic pressure-volume relationship fails to account the thermal damping due to heat transfer through the bubble wall because P b dV b is a perfect differential and consequently its integral over a cycle vanishes (Prosperiretti et al, 1988) where P b is the gas pressure inside the bubble and V b is the bubble volume. Furthermore, the polytropic approximation assumes the uniform temperature for the gas intrinsically, which is valid only for a particular case and it is hard to tell whether the gas inside the bubble oscillating under ultrasound behaves isothermally or adiabatically (Loefstedt et al, 1993). In this study, we have formulated a general bubble dynamics model, which is as follows.…”
Section: Introductionmentioning
confidence: 99%
“…The Rayleigh-Taylor equation (Rayleigh 1917) augmented with an expression for viscosity, surface tension, an incident sound wave (Rayleigh/Plesset/Noltingk/Neppiras/Poritsky) (Lauterborn 1976) and radiation damping (Löfstedt et al 1993) is frequently used. An equation with a more complete modelling of radiation damping is the one from Keller & Miksis (1980) (see also Brennen 1995)…”
Section: Radial Oscillations (A) the Gilmore Equationmentioning
confidence: 99%